Relação da tolerância ao déficit hídrico com o teor e acúmulo de nitrogênio, fósforo e potássio em cultivares de cana-de-açúcar - Silva, Thais Ramos da [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
In regions where expansion of sugarcane in Brazil will occur in the coming years an increase in the occurrence of extreme events such as the driest years. It then becomes important to the use of varieties tolerant to water stress in these new areas. The present study aimed to define the degree of tolerance to drought of three varieties of sugarcane by means of physiological variables and the relation of tolerance of these varieties with the content and accumulation of N, P and K. The experiment was conducted in pots containing a 50 dm3 Typic Haplustox. The experimental design was randomized blocks, with nine treatments (3 varieties x 3 water potential of the soil) with four replications. With 60 days of age the SP81-3250 varieties, RB855453 and IACSP95-5000 were submitted to the three soil water potential: Ψno restriction (-0.010 to -0.015 MPa), Ψmoderate (-0.050 to -0.055 MPa) and Ψsevere (-0.075 to -0.080 MPa) and evaluated at three times: 30, 60 and 90 days after treatment imposition. The variables analyzed were: number of green leaves, leaf area, plant height, number of tillers, leaf water potential, SPAD index, photosynthesis, transpiration, stomatal conductance, internal CO2 concentration, instantaneous carboxylation efficiency, instant use efficiency water, intrinsic water use efficiency, phytomass, N in the leaves, N in the stalks, N accumulation, P in the leaves, P in the stalks, P accumulation, K in the leaves, K in the stalks, K accumulation and N, P and K utilization efficiency. There were lower values in plants of the varieties Ψsevere compared to plants under Ψno restriction the variables: number of green leaves, leaf area, plant height, number of tillers, SPAD index, photosynthesis, transpiration, stomatal conductance, instant efficiency carboxylation, intrinsic efficiency of water use, instantaneous water use efficiency, phytomass, N, P and K in the leaves ...

Nas regiões em expansão da cana-de-açúcar no Brasil deverá ocorrer nos próximos anos um aumento na ocorrência de eventos extremos, como anos mais secos. Torna-se, então importante a utilização de cultivares tolerantes à deficiência hídrica nessas novas áreas. Assim, o presente estudo teve por objetivo definir o grau de tolerância ao déficit hídrico de três cultivares de cana-de-açúcar por meio de variáveis fisiológicas e verificar a relação da tolerância destas cultivares com o teor e acúmulo de N, P e K. O experimento foi conduzido em vasos de 50 dm3 contendo um Latossolo Vermelho distrófico típico, textura média. O delineamento experimental foi em blocos casualizados, com 9 tratamentos (3 cultivares x 3 potenciais hídricos do solo), com quatro repetições. Com 60 dias de idade as cultivares SP81-3250, RB855453 e IACSP95-5000 foram submetidas aos três potenciais hídricos do solo: ΨSR (-0,010 a -0,015 MPa), ΨM (-0,050 a -0,055 MPa) e ΨS (-0,075 a -0,080 MPa) e avaliadas em três épocas: 30, 60 e 90 dias após a imposição dos tratamentos. As variáveis avaliadas foram: número de folhas verdes, área foliar, altura da planta, número de perfilhos, potencial hídrico foliar, índice SPAD, fotossíntese, transpiração, condutância estomática, concentração interna de CO2, eficiência instantânea de carboxilação, eficiência instantânea de uso da água, eficiência intrínseca de uso da água, fitomassa, N nas folhas, N nos colmos, acúmulo de N, P nas folhas, P nos colmos, acúmulo de P, K nas folhas, K nos colmos, acúmulo de K e eficiência de utilização de N, P e K. Verificaram-se menores valores nas plantas das cultivares sob ΨS em relação às plantas sob ΨSR nas variáveis: número de folhas verdes, área foliar, altura da planta, número de perfilhos, índice SPAD, fotossíntese, transpiração, condutância estomática, eficiência instantânea de carboxilação, eficiência intrínseca...
Keywords: Cana-de-açúcar; Nutrientes; Plantas - Efeito da umidade do solo; Irrigação com déficit hídrico; Plantas cultivares